2019
DOI: 10.2340/00015555-3315
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Associated Diseases, and Management of Gram­negative Toe-web Infection: A French Experience

Abstract: Gram-negative toe-web infection is a disabling painful disease with long healing time and high recurrence rate. In a French retrospective real-life study, we described features and management of Gram-negative toe-web infection and evaluated the effect of controlling predisposing factors/diseases on the rate of recurrence. Among the 62 patients included, mainly male, 31 experienced more than one episode. Pseudomonas aeruginosa was the prominent bacteria. Predisposing factors/associated diseases were eczema, sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(32 citation statements)
references
References 9 publications
4
13
1
Order By: Relevance
“…The genus Pseudomonas, enriched with psoriatic skin, includes many opportunistic pathogens and contributes to the treatment response of psoriasis patients treated with narrowband ultraviolent B (UVB) (Assarsson et al, 2018). For example, the most prominent bacteria of Gram-negative toe-web infection, Pseudomonas aeruginosa, is closely associated with the incidence of psoriasis (Goiset et al, 2019). Chang et al (2018) also found that microbial communities in psoriatic lesions tended to display higher alpha diversity and greater heterogeneity but lower stability than healthy skin microbial communities.…”
Section: Skin Dysbiosis In Psoriasismentioning
confidence: 99%
“…The genus Pseudomonas, enriched with psoriatic skin, includes many opportunistic pathogens and contributes to the treatment response of psoriasis patients treated with narrowband ultraviolent B (UVB) (Assarsson et al, 2018). For example, the most prominent bacteria of Gram-negative toe-web infection, Pseudomonas aeruginosa, is closely associated with the incidence of psoriasis (Goiset et al, 2019). Chang et al (2018) also found that microbial communities in psoriatic lesions tended to display higher alpha diversity and greater heterogeneity but lower stability than healthy skin microbial communities.…”
Section: Skin Dysbiosis In Psoriasismentioning
confidence: 99%
“…Interdigital infection is a spectrum of relatively common, troubling, and neglected disorders [3], especially in the humid and rainy climates of southern China. It was rst described as a speci c dermatologic entity by Amonette and Rosenberg in 1973 [5]. A variety of terms have been used to describe this disorder, including gram-negative bacterial toe web infection, which is characterized as an acute bacterial infection of the toe web spaces due to Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…With high recurrence rates and possible complications, such as immobility, cellulitis, wound healing disorders, and autosensitization dermatitis, interdigital infections present a frequent therapeutic challenge in clinical practice [4,5,18]. However, data supporting a standardized regimen remain insu cient [19].…”
Section: Discussionmentioning
confidence: 99%
“…They recorded predisposing factors that included eczema and psoriasis, suspected tinea pedis and exposure to humidity or hyperhidrosis and vascular disorders. Five percent of those studied were diabetic, an interesting observation given the growing association between foot Gram negative bacteria and diabetic foot ulceration or diabetic foot studied using mixed techniques of culture plus 16S ribosomal RNA (16SrRNA) genetic analysis (7). The French study included patients with a severe spectrum of disease and over 75% had more than one episode of Gram negative infection, often following failure of initial outpatient management.…”
Section: Gram Negative Toe Web Infection -A Not So Rare But Neglectedmentioning
confidence: 99%